Analysis of customer relationship management and service quality on customer loyalty - Arbi Siti Rabiah; Akmal Rizki Fadillah (Jurnal Mantik, 2023)
This study discusses the variables that can affect the loyalty of the company to the company that is currently researched, which is PT Dua Benua Pratama. The aim of this study is to analyze Customer Relationship Management and Service Quality and Customer Loyalty at PT Dua Benua Pratama. This study was carried out on 101 respondents who were partners from PT Dua Benua Pratama. In the analysis of the data, this study used SPSS with the linear regression method. The conclusion of this study is that there is an influence between Customer Relationship Management and Service Quality and Customer Loyalty on PT Dua Benua Pratama. The use of CRM can help companies in understanding customer needs better,ining good communication and building customer trust, thus increasing customer loyalty. In addition, good service quality can also increase customer satisfaction and strengthen the emotional bond with the brand, thereby increasing customer loyalty. The practical implications of this research are that companies can improve CL by using the right CRM strategy and focusing on quality service.